Evaluasi Skrining pada Pasien Karies Gigi di Wilayah Kerja Puskesmas Kluet Timur Aceh Selatan - Ekasusanti Ekasusanti; Basri Aramico; Radhiah Zakaria (Yayasan Literasi Sains Indonesia, 2026)
Dental caries screening plays an essential role in identifying high-risk individuals, detecting early caries lesions, and supporting appropriate preventive and therapeutic interventions. This study aimed to evaluate the implementation of dental caries screening among patients in the working area of Kluet Timur Community Health Center, South Aceh. Methode is descriptive evaluative study with a quantitative approach was conducted. The study population included all patients receiving dental examinations within the service area of Kluet Timur Community Health Center, with samples selected through purposive sampling. Data were obtained through direct observation, document review, and screening evaluation instruments. The collected data were analyzed using descriptive analysis. The findings indicated that dental caries screening activities had been carried out in accordance with established procedures, including oral examinations, documentation of clinical findings, and the determination of appropriate follow-up care. However, several obstacles were identified, including limited healthcare resources, insufficient public awareness regarding regular dental examinations, and incomplete documentation of screening outcomes. Overall, the implementation of dental caries screening at Kluet Timur Community Health Center was categorized as adequate and supported early detection of dental caries cases. The concludes that although the screening program has been implemented effectively, improvements are still needed, particularly in strengthening documentation systems, enhancing oral health education, and improving patient follow-up monitoring. Continuous evaluation and development of oral health promotion strategies are recommended to optimize the effectiveness of dental caries screening services.